The effect of running experience and speed on local dynamic stability in running - Cerrito, Adrien; Wittwer, Larissa; Schmitt, Kai-Uwe (Frontiers in Sports and Active Living, 2025)
IntroductionAs a coach or health care professional working with physically active people, it can be difficult to guide runners towards safe and effective progression, because making changes to single aspects of running technique may not lead to the desired result. Alternatively, it has been proposed to consider the human body as one complex system when assessing and improving human movement. From this perspective, it appears that the movement variability and local dynamic stability, expressed as the maximum Lyapunov exponent (LyEmax), may be of particular interest. This study investigated the difference in LyEmax of the lower extremities' main joints (ankle, knee, hip) between experienced and novice runners at different running speeds.MethodsThirty-six participants were recruited, with 18 experienced runners and 18 novice runners. Participants ran at three different speeds on a treadmill for 10 minutes in each of the following conditions: preferred running speed, 10% slower, and 10% faster. Twenty-six participants were included in the analysis. The LyEmax was calculated from joint kinematics and a two-way ANOVA with repeated measures was applied.ResultsThe results showed that there is a strong effect of running experience on the LyEmax with the experienced runners having more local dynamic stability. The effect of running speed was statistically significant only for the hip joint, where higher running speeds resulted in more local dynamic stability in both groups.Discussion and conclusionThe results should be interpreted with caution, particularly due to the low running speeds chosen by the novice runners. Nevertheless, the study's findings support the emerging view that movement variability is a parameter on which it is important to focus, and that local dynamic stability should be improved in novice runners as well as with athletes or patients who are in a return-to-sport phase of a rehabilitation.